Antibody-independent identification of bovine milk-derived peptides in breast-milk. Issue 8 (11th July 2016) - Picariello, Gianluca; Addeo, Francesco; Ferranti, Pasquale; Nocerino, Rita; Paparo, Lorella; Passariello, Annalisa; Dallas, David C.; Robinson, Randall C.; Barile, Daniela; Canani, Roberto Berni
Abstract : For the first time, peptides derived from the digestion of bovine milk allergens (β-lactoglobulin and αs1 -casein) have been identified in breast milk, using HPLC-mass spectrometry. Abstract : Exclusively breast-fed infants can exhibit clear signs of IgE or non IgE-mediated cow's milk allergy. However, the definite characterization of dietary cow's milk proteins (CMP) that survive the maternal digestive tract to be absorbed into the bloodstream and secreted into breast milk remains missing. Herein, we aimed at assessing possible CMP-derived peptides in breast milk. Using high performance liquid chromatography (HPLC)-high resolution mass spectrometry (MS), we compared the peptide fraction of breast milk from 12 donors, among which 6 drank a cup of milk daily and 6 were on a strict dairy-free diet. We identified two bovine β-lactoglobulin (β-Lg, 2 out 6 samples) and one αs1 -casein (1 out 6 samples) fragments in breast milk from mothers receiving a cup of bovine milk daily. These CMP-derived fragments, namely β-Lg (f42–54), (f42–57) and αs1 -casein (f180–197), were absent in milk from mothers on dairy-free diet. In contrast, neither intact nor hydrolyzed β-Lg was detected by western blot and competitive ELISA in any breast milk sample. Eight additional bovine milk-derived peptides identified by software-assisted MS were most likely false positive. The results of this study demonstrate that CMP-derived peptides rather than intact CMP may sensitize or elicit allergic responses in the neonate through mother's milk. Immunologically active peptides from the maternal diet could be involved in priming the newborn's immune system, driving a tolerogenic response.